2009
DOI: 10.2202/1548-923x.1645
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Addictions: Toward Curricular Change for Family Nurse Practitioners

Abstract: The purpose of this paper is to describe the results of a survey of advanced practice nurses (APNs) to determine the activities they perform related to caring for patients with addictions and or co-occurring mental health disorders, the amount of addictions education in their graduate programs, and their perceptions of the value of addictions education for their role. Data were obtained from 233 APNs in New York State using a tool adapted from a previous job analysis survey. APNs reported the greatest amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, like most healthcare professionals, including physicians, nurses typically receive little training in how to address alcohol use (Association for Medical Education and Research in Substance Abuse, 2005). Unhealthy alcohol use traditionally receives cursory attention in undergraduate and graduate nursing curricula (Campbell-Heider et al, 2009;Keller & Dermatis, 1999;Mollica, Hyman, & Mann, 2011), leaving most nurses with inadequate clinical knowledge, skills, and motivation for effectively addressing this issue (Broyles et al, 2012a;Happell & Taylor, 1999;Naegle, 2002). Furthermore, little education and skills training are offered to nurses regarding how to screen for unhealthy alcohol use, how to engage patients and discuss reducing alcohol consumption to levels recommended by the National Institute on Alcohol Abuse and Alcoholism (NIAAA, 2005), and how and when to refer a patient for more comprehensive assessment and/or treatment (Broyles et al, 2012a;Mollica et al, 2011).…”
mentioning
confidence: 99%
“…However, like most healthcare professionals, including physicians, nurses typically receive little training in how to address alcohol use (Association for Medical Education and Research in Substance Abuse, 2005). Unhealthy alcohol use traditionally receives cursory attention in undergraduate and graduate nursing curricula (Campbell-Heider et al, 2009;Keller & Dermatis, 1999;Mollica, Hyman, & Mann, 2011), leaving most nurses with inadequate clinical knowledge, skills, and motivation for effectively addressing this issue (Broyles et al, 2012a;Happell & Taylor, 1999;Naegle, 2002). Furthermore, little education and skills training are offered to nurses regarding how to screen for unhealthy alcohol use, how to engage patients and discuss reducing alcohol consumption to levels recommended by the National Institute on Alcohol Abuse and Alcoholism (NIAAA, 2005), and how and when to refer a patient for more comprehensive assessment and/or treatment (Broyles et al, 2012a;Mollica et al, 2011).…”
mentioning
confidence: 99%
“…A concern may be the lack of such content in nursing curricula. For example, a study of advanced practice nurses found that while they engaged in obtaining historical data related to addictions, they were less apt to utilize standardized screening tools, and reported low utilization of evidence-based educational and treatment strategies (Campbell-Heider et al, 2009). Likewise, nurses should be educated about detecting symptoms of depression such as irritability, anhedonia, changes in sleeping patterns, or feelings of worthlessness (Son & Kirchner, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the absence of substance use education seen in nursing undergraduate programs, graduate nursing programs are also deficient in substance use education (Covington et al, 2018;Moore et al, 2017;Savage et al, 2018). A survey of 233 advanced practice nurses across specialties found that respondents reported receiving 1.67 (standard deviation [SD] ¼ 1.13) hours of didactic content related to addiction in their graduate programs, with the modal response that no addiction-related content had been included in the curriculum (Campbell-Heider et al, 2009). In this respect, nursing students fare worse than the preparation of our medical colleagues.…”
Section: Addiction-related Contentmentioning
confidence: 99%